"I fought my entire way": Experiences of declining maternity care services in British Columbia. - P Mimi Niles (Public Library of Science (PLoS), 2021)
Background The 2016 WHO Standards for improving quality of maternal and newborn care in health facilities established patient experience of care as a core indicator of quality. Global health experts have described loss of autonomy and disrespect as mistreatment. Risk of disrespect and abuse is higher when patient and care provider opinions differ, but little is known about service users experiences when declining aspects of their maternity care. Methods To address this gap, we present a qualitative content analysis of 1540 written accounts from 892 service users declining or refusing care options throughout childbearing with a large, geographically representative sample (2900) of childbearing women in British Columbia who participated in an online survey with open-ended questions eliciting care experiences. Findings Four themes are presented: 1) Contentious interactions: "I fought my entire way", describing interactions as fraught with tension and recounting stories of "fighting" for the right to refuse a procedure/intervention; 2) Knowledge as control or as power: "like I was a dim girl", both for providers as keepers of medical knowledge and for clients when they felt knowledgeable about procedures/interventions; 3) Morbid threats: "do you want your baby to die?", coercion or extreme pressure from providers when clients declined interventions; 4) Compliance as valued: "to be a 'good client'", recounting compliance or obedience to medical staff recommendations as valuable social capital but suppressing desire to ask questions or decline care. Conclusion We conclude that in situations where a pregnant person declines recommended treatment, or requests treatment that a care provider does not support, tension and strife may ensue. These situations deprioritize and decenter a woman's autonomy and preferences, leading care providers and the culture of care away from the principles of respect and person-centred care.